Legal Protection of Victims of Trafficking in Persons in the Criminal Justice System in Indonesia - Sabono, Adriana; Setiyono, Joko (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Human Trafficking is a modern crime related to human slavery which has become a focus not only in Indonesia, but also in developing countries and also in the United Nations. The crime of trafficking in persons in Indonesia has happened a lot and is not a strange thing to discuss. Cases in Indonesia can also be said to be many. The 7th United Nations Congress held in Milan in 1985 also discussed the rights of victims. The rights of victims of trafficking in persons in SPP are also protected. Some of the judge's decisions that impose sanctions on convicts are restitution. Restitution itself is one of the rights of victims which is regulated in Law Number 21 of 2007 concerning the Eradication of the Criminal Acts of Trafficking in Persons.